Analisis Hubungan Kuantitatif Struktur dan Aktivitas untuk Merancang Insektisida Baru Turunan Karbamat Menggunakan Metoda Semiempirik PM3 - Ananto, Agus Dwi (Al-Kimia, 2017)
A research has been conducted to investigate the HKSA equation model of a set of carbamic derivative insecticidal compounds based on the hydrofobic, electronic and steric descriptors. The descriptors are calculated by a method of PM3 while the the insecticidal activity are obtained by the experiment. The relationship of the descriptos and the activities are determined by multilinear reggression analysis. The result of the analysis then provide a best equation model that can be used to design new carbamic derivative insecticidal compounds. These design might be recommended to be synthesized in the experimental works.